The impact of devolutionary reform on teachers and principals - Fitzgerald, Scott; Wilson, Rachel; McGrath-Champ, Susan; Stacey, Meghan; Gavin, Mihajla (New South Wales Teachers' Federation, 2023)
Scott Fitzgerald et al. reflect on the shift from centralised decision-making to increased school autonomy and the resultant impact on teachers and principals.